Management and Prospects of the Croatian Short Sea Shipping Development - Bukljaš, Mihaela; Jolić, Natalija; Jolić, Ante (Promet - Traffic&Transportation, 2007)
Quite a number of scientific and technical papers havebeen written about the elements and the factors of the portsystem operation in the developed maritime countries. Thestudy of a port system may be based on the research of thetraffic, commercial and industrial role separately, or in an integratedapproach of the technical, technological, organisational,economic, ecological and legal elements. The drawbacksof both approaches come to the fore if one studies thecompetitiveness of the port system as the end goal of the portfunctioning which also determines the operation of the portsystem subjects. A comprehensive study of the competitivenessof the Croatian port system must combine the study and researchof the possibilities of sh011 sea shipping integration inthe European maritime countries, especially regarding theCroatian integration into the European Union. From the Croatianaspect, the term as accepted by the Ministry of the Sea,Tourism, Transportation and Development, ’meduobalnoprometno povezivanje’ (English: short sea shipping) has multiplemeaning, and this is primarily the traffic connection ofthe Croatian and Italian coasts, redirection of a part of cargotransported from the European Union to the countries of theSouth-eastern Balkan, via Croatia, reduction of harmfulemissions in traffic and increase of traffic in domestic ports.’Meduobalna plovidba’ (Eng. intercoastal navigation) refersto the movement of goods and passengers by sea between theports located in Europe or between these ports and those outsideEurope having the sea border with Europe. The goal ofintroducing short sea shipping is to alleviate the burden on theEuropean road routes and to redirect the transport of part ofthe cmgo and passengers to sea transport; and furthermore,the improvement of the traffic connections between Croatiaand the European Union and connecting of the Danube andthe Adriatic.